2001
DOI: 10.1159/000047398
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefit and Approach of Ultrafiltration in Acute Heart Failure

Abstract: Because of the increasing incidence of acute heart failure admissions to critical care units, nephrologists have been asked to become more involved in the management of these patients. Renal dysfunction is a major element in impeding clinical recovery. In acute heart failure, renal function is often abnormal. The judicious application of ultrafiltration techniques may represent an efficacious adjunct to present conventional practice. In patients with refractory congestive heart failure, the ability to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 27 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…Over the next 3 decades, several investigators reported favorable results with regard to the efficacy and safety of this therapy (36). In one of the largest of these studies, Canaud et al used slow UF (continuous or daily) in 52 patients with severe congestive HF (class IV of the New York Heart Association classification) (37).…”
Section: Renal Replacement Therapy For Heart Failure: Earlier Clinicamentioning
confidence: 99%
See 1 more Smart Citation
“…Over the next 3 decades, several investigators reported favorable results with regard to the efficacy and safety of this therapy (36). In one of the largest of these studies, Canaud et al used slow UF (continuous or daily) in 52 patients with severe congestive HF (class IV of the New York Heart Association classification) (37).…”
Section: Renal Replacement Therapy For Heart Failure: Earlier Clinicamentioning
confidence: 99%
“…Although an improvement in natriuresis and renal function was also observed in a subset of patients, the findings were variable and not as prominent as those related to cardiac status. It is noteworthy that not all earlier studies, which were either case reports or had small patient populations without a control group, performed isolated UF; some used other modalities such as continuous venovenous hemofiltration or hemodiafiltration (36). Because these therapies provide significant clearance in addition to extraction of fluid, their results should be cautiously interpreted to avoid unjustified extrapolation.…”
Section: Renal Replacement Therapy For Heart Failure: Earlier Clinicamentioning
confidence: 99%
“…23 UF is a process by which plasma water is separated from whole blood by convective solute transport. 24 Hydrostatic forces are applied to whole blood across a semi permeable membrane to create an ultrafiltrate that is isosmotic to plasma water. 4,25 This differs from hemodialysis in which solutes flow down a concentration gradient and significant shifting of electrolytes, particularly sodium and potassium, can occur.…”
Section: Uf For Treatment Of Congestion In Hfmentioning
confidence: 99%
“…This is not a widely used strategy and should only be used under the supervision of a physician with extensive expertise in its application. Several small studies have shown that ultrafiltration (slow continuous venovenous method or traditional dialysis) can be very effective in fluid removal and symptom improvement in a few highly selected patients with severe renal insufficiency and volume overload (104)(105)(106)(107)(108). These seem to be most effective when renal function is severe but stable, rather than acute.…”
Section: Practical Tipsmentioning
confidence: 99%
“…This is in contrast to the acute intravenous administration of a betablocker to naïve patients in the acute myocardial infarction setting. There are no data regarding the use of beta blockade in cardiogenic shock because in most cases, clinicians will withhold in this setting (100,(106)(107)(108)(109)(110)(111)(112)(113)128).…”
Section: Practical Tipsmentioning
confidence: 99%